Amanita wadulawitu (Basidiomycota), a new species from Western Australia, and an expanded description of A. kalamundae - McGurk, Laurton; Giustiniano, D.; Davison, Elaine; Watkin, Elizabeth (Department of Environment and Conservation, WA, 2016)
A new species of Amanita Pers. is documented from Western Australia. Amanita wadulawitu L.E.McGurk, E.M.Davison & E.L.J.Watkin is described from the Perth IBRA subregion. Amanita kalamundae O.K.Mill. is redescribed to include additional collections, drawing attention to the presence of clamp connections in the lamellae and at the base of basidia. A BLASTn search has shown that there are no exact matches of the nuclear ribosomal internal transcribed spacer (ITS) region of either species in GenBank.